Liberia : Enhanced Initiative for Heavily Indebted Poor Countries-Completion Point Document and Multilateral Debt Relief Initiative. (IMF Staff Country Reports; Country Report ;, 2010)
The Liberia Poverty Reduction Strategy (LPRS) was completed in March 2008. Since reaching the decision point in March 2008, Liberia has maintained macroeconomic stability. The global financial crisis adversely impacted Liberia shortly after the LPRS was released. Investments were postponed, and export revenues were sharply reduced in the rubber sector as external demand weakened. The authorities' strict adherence to a cash-based balanced budget, in place since February 2006, has contributed substantially to regaining fiscal discipline, putting debt on a downward path while also increasing pro-poor expenditures.